Cardiac Remodeling Induced by All-Trans Retinoic Acid is Detrimental in Normal Rats - Silva, Renata A. C. [UNESP]; Gonçalves, Andréa F. [UNESP]; Dos Santos, Priscila P. [UNESP]; Rafacho, Bruna [UNESP]; Claro, Renan F. T. [UNESP]; Minicucci, Marcos F. [UNESP]; Azevedo, Paula S. [UNESP]; Polegato, Bertha F. [UNESP]; Zanati, Silméia G. [UNESP]; Fernandes, Ana Angélica [UNESP]; Paiva, Sergio A. R. [UNESP]; Zornoff, Leonardo A. M. [UNESP] (Karger Publishers, 2017)
Background/Aims: This study aimed to discern whether the cardiac alterations caused by retinoic acid (RA) in normal adult rats are physiologic or pathologic. Methods and Results: Wistar rats were assigned into four groups: control animals (C, n = 20) received a standard rat chow; animals fed a diet supplemented with 0.3 mg/kg/day all-trans-RA (AR1, n = 20); animals fed a diet supplemented with 5 mg/kg/day all-trans-RA (AR2, n = 20); and animals fed a diet supplemented with 10 mg/kg/day all-trans-RA (AR3, n = 20). After 2 months, the animals were submitted to echocardiogram, isolated heart study, histology, energy metabolism status, oxidative stress condition, and the signaling pathway involved in the cardiac remodeling induced by RA. RA increased myocyte cross-sectional area in a dose-dependent manner. The treatment did not change the morphological and functional variables, assessed by echocardiogram and isolated heart study. In contrast, RA changed catalases, superoxide dismutase, and glutathione peroxidases and was associated with increased values of lipid hydroperoxide, suggesting oxidative stress. RA also reduced citrate synthase, enzymatic mitochondrial complex II, ATP synthase, and enzymes of fatty acid metabolism and was associated with increased enzymes involved in glucose use. In addition, RA increased JNK 1/2 expression, without changes in TGF-β, PI3K, AKT, NFκB, S6K, and ERK. Conclusion: In normal rats, RA induces cardiac hypertrophy in a dose-dependent manner. The non-participation of the PI3K/Akt pathway, associated with the participation of the JNK pathway, oxidative stress, and changes in energy metabolism, suggests that cardiac remodeling induced by RA supplementation is deleterious.
Keywords: Cardiac function; Energy metabolism; Hypertrophy; Retinoic acid